Macroautophagy and the Oncogene-Induced Senescence - Grasso, Daniel; Vaccaro, Maria I. (Frontiers in Endocrinology, 2014)
The oncogene-induced senescence is emerging as a potent tumor suppressor mechanism and as a possible therapeutic target. Macroautophagy is intimately linked to the senescence condition setup, although its role has not been elucidated yet. Here we discuss up-to-date concepts of senescence-related macroautophagy and evaluate the current trend of this growing research field, which has relevance in future perspectives towards therapeutic options against cancer.